Chemical Modification of Polysaccharides. (10th September 2013) - Cumpstey, Ian
Abstract : This review covers methods for modifying the structures of polysaccharides. The introduction of hydrophobic, acidic, basic, or other functionality into polysaccharide structures can alter the properties of materials based on these substances. The development of chemical methods to achieve this aim is an ongoing area of research that is expected to become more important as the emphasis on using renewable starting materials and sustainable processes increases in the future. The methods covered in this review include ester and ether formation using saccharide oxygen nucleophiles, including enzymatic reactions and aspects of regioselectivity; the introduction of heteroatomic nucleophiles into polysaccharide chains; the oxidation of polysaccharides, including oxidative glycol cleavage, chemical oxidation of primary alcohols to carboxylic acids, and enzymatic oxidation of primary alcohols to aldehydes; reactions of uronic-acid-based polysaccharides; nucleophilic reactions of the amines of chitosan; and the formation of unsaturated polysaccharide derivatives.